Union Budget 2018: reforms in Indian Agriculture - Kumar, Shiv; Chahal, V. P.; Jhajharia, Abimanyu (Indian Farming, 2018)
The Indian farmer faces more marketing problems than production of the crops. Middlemen are the bane of Indian agriculture.The information needs to be disseminated to stakeholders rigorously at regular period to take decisions for sale of the produce. The staff of the line department be delegated the job of tying up farmer produce with appropriate regional markets and the Processing Industry for the best price realization. Cultivation of high value agriculture/ crops in clusters bring advantages of scales of operations and can spur establishment of entire chain from production to marketing, besides giving recognition to the districts for specific crops. A farm to fork approach entails several activities which fall in jurisdiction of several ministries that generates impediments and risks in agricultural management. Budget will consolidate gains with focus on strengthening agriculture economy and ensure benefits reach eligible beneficiaries. The intent of government on implementation of a series of fundamental structure reforms in agriculture is going to overcome the agrarian crisis to an extent. However, the magnitude of benefits of reforms will become evident with time only.